2011
DOI: 10.1111/j.1474-9726.2011.00705.x
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association study identifies a single major locus contributing to survival into old age; the APOE locus revisited

Abstract: SummaryBy studying the loci that contribute to human longevity, we aim to identify mechanisms that contribute to healthy aging. To identify such loci, we performed a genomewide association study (GWAS) comparing 403 unrelated nonagenarians from long-living families included in the Leiden Longevity Study (LLS) and 1670 younger population controls. The strongest candidate SNPs from this GWAS have been analyzed in a meta-analysis of nonagenarian cases from the Rotterdam Study, Leiden 85-plus study, and Danish 190… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
210
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 260 publications
(222 citation statements)
references
References 66 publications
10
210
1
1
Order By: Relevance
“…Consistent with previous studies (Deelen et al., 2011; Fortney et al., 2015), our association analyses showed that minor alleles of rs2075650 and rs157580 ( TOMM40 ) were associated with higher and lower risk of AD development, respectively (Table S2). The effect directions were consistent in all studies; the effect sizes varied markedly, ranging from 0.380 ( p  = 0.014) in the FHS cohort to 1.45 ( p  = 1.65 × 10 −78 ) in the LOADFS cohort for rs2075650 and from −0.052 ( p  = 0.612) in the FHS cohort to −0.705 ( p =  5.98 × 10 −23 ) in the LOADFS cohort for rs157580 (Figure S1 and Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with previous studies (Deelen et al., 2011; Fortney et al., 2015), our association analyses showed that minor alleles of rs2075650 and rs157580 ( TOMM40 ) were associated with higher and lower risk of AD development, respectively (Table S2). The effect directions were consistent in all studies; the effect sizes varied markedly, ranging from 0.380 ( p  = 0.014) in the FHS cohort to 1.45 ( p  = 1.65 × 10 −78 ) in the LOADFS cohort for rs2075650 and from −0.052 ( p  = 0.612) in the FHS cohort to −0.705 ( p =  5.98 × 10 −23 ) in the LOADFS cohort for rs157580 (Figure S1 and Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…People who carry APOE ε4 allele have an increased risk of developing AD, while APOE ε2 carriers are protected from the disease (Deelen et al ., 2011). The level of soluble ApoE protein increases both in patients with AD and in APP/PS1 rat model of AD (Arold et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, two loci that are repeatedly found by GWAS of aging are APOE (Deelen et al, 2011; Ewbank, 2007; Gerdes, Jeune, Ranberg, Nybo, & Vaupel, 2000) and FOXO3A (Anselmi et al, 2009; Flachsbart et al, 2009; Li et al, 2009; Pawlikowska et al, 2009; Willcox et al, 2008). Similar to AD, APOE ε2 is found to be enriched in elderly and centenarians compared to younger individuals (Seripa et al, 2006).…”
Section: Molecular Links Between Aging and Admentioning
confidence: 99%